1983
DOI: 10.1017/s0022029900023001
|View full text |Cite
|
Sign up to set email alerts
|

Alkylglycerols in bovine colostrum and milk in relation to precursor levels

Abstract: The concentrations of dihydroxyacetone phosphate (DHAP), glycerol-3-phosphate (GP), glucose and alkylglycerols were measured in bovine colostrum and milk. Concentrations of GP were higher in colostrum than in milk, and corresponded to intracellular concentrations at the onset of lactation. This suggests that GP equilibrates over the apical membrane at onset of lactation, which is believed to occur also in full lactation. The ratio of DHAP to GP showed a peak in colostrum that was more than twice that in milk, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It is known that Agmo transcription is diminished by M1-activating stimuli (26, 62) (Supplemental Figure 15, C and D), whereas M2 polarizing signals increase Agmo transcription in ATMs (62). Accordingly, we found that IL-4/STAT6 signaling controlled Agmo transcription and AGMO was expressed and localized to intracellular membranes in IL-4-treated macrophages (Supplemental Figure 15, E and F), which serve as the site of AKG accumulation and PAF synthesis (24,28,68,69).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…It is known that Agmo transcription is diminished by M1-activating stimuli (26, 62) (Supplemental Figure 15, C and D), whereas M2 polarizing signals increase Agmo transcription in ATMs (62). Accordingly, we found that IL-4/STAT6 signaling controlled Agmo transcription and AGMO was expressed and localized to intracellular membranes in IL-4-treated macrophages (Supplemental Figure 15, E and F), which serve as the site of AKG accumulation and PAF synthesis (24,28,68,69).…”
Section: Discussionmentioning
confidence: 52%
“…Cow milk contains negligible AKGs, which is at odds with the finding of AKG synthesis and release in cow colostrum and milk (68). This may be due to an increased catabolism of AKGs in cow milk (24). Moreover, the amount of milk produced daily by a dairy cow is magnitudes higher than of the other species tested and may lead to the dilution of AKG concentration to a negligible level.…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation